Madkhali’s criticism of Sayyid Quṭb: a critique of the critique - Arikewuyo, Nafiu Ahmed (Universitas Ahmad Dahlan, 2023)
From the 60s of the 20th century, the works of Sayyid Quṭb have enormous influence on the thought of Muslim youths and Islamists. The core message of his works is establishing the supremacy of Islamic law in all facets of life and outright condemnation of the subsisting order of the day concerning the political and socio-economic operations in Muslim nations. The effect of his thoughts on Muslim youths is visible in the resurrection of Islamists who have become a thorn in the flesh of political dictators and autocratic monarchs in Arabia. As part of efforts to neutralize the effects of Quṭb’s works on the ever-increasing Muslim youths in Saudi particularly and the Muslim world at large, Rabi’u Madkhali, a senior Salafi diehard with much influence in Madinah, kickstarted the project of refuting what he termed as